Study on the Applicability of Needle/Cone Penetration Experiment for Asphalt-Rubber. (24th September 2020) - Yao, Zechen; Yang, Renfeng; Liu, Zhonglin; An, Haichao; Zhang, Qingzhe; Yuan, Wei
Abstract : In order to quantitatively study the applicability of needle/cone penetration experiment for asphalt-rubber (AR), the dynamic model of needle/cone in penetration process was established based on the Kelvin model, and the different impacts of crumb rubber (CR) particles on needle/cone penetration depth were analyzed using Matlab . The probability of needle/cone contacting CR particles in penetration process was statistically calculated. AR binders with different CR particle sizes were observed using scanning electron microscope (SEM) and prepared for testing needle/cone penetration. The results showed that the solid-liquid two-phase feature of AR binders gradually weakened with the reduction of CR particle size. At the same viscoelastic parameters, CR particles had little impact on cone penetration depth when cone contacted CR particles. The probability of cone contacting CR particles was close to 100% in penetration process while that of needle was around 50%. The standard deviations of the needle penetration experimental results for AR binders with #20, #30, #40, #60, and #80 mesh CR were 4.0, 3.8, 2.8, 1.1, and 1.1 times of cone penetration, respectively. This study shows that the cone penetration experiment has a significant advantage in evaluating the consistency of the AR binder with coarse CR.